Study Effects of Contraceptives On Serum Electrolytes and lipid profile in Samarra City - Naji Muhsin, Saria; Saad Yasen, Aya; Faris Rija, Firas (University of Thi-Qar Journal of Science, 2019)
This study included ( 150 ) samples of women used Contraceptives in (Samaraa General Hospital) (30) blood draw pulled from healthy women as Control sample. The samples were divided into three groups; the first group: -(60) women used combined oral contraceptive pill (COCs) the second group: -(60) women used Progesterone Only Pills(POPs). The third group was the healthy women. The results of the study indicated significant numbers decrease in the Concentration of the Potassium Ion at level (P <0.001) and significant increase in the Concentration of the Sodium Ion at level (P <0.001) when compared to the control group. The results revealed significant decrease in the proteins of the blood (Total protein, Albumin) at level (P <0.001)when compared to the control group. while the results showed a rise in the concentration level of Cholesterol, Triglyceride at level (P <0.001)and significant decrease in the HDL when compared to the control group.